Effect of Glyceraldehyde Cross-Linking on a Rabbit Bullous Keratopathy Model - Mengmeng Wang (Journal of Ophthalmology)
Background. To evaluate the effects of corneal glyceraldehyde CXL on the rabbit bullous keratopathy models established by descemetorhexis. Methods. Fifteen rabbits were randomly divided into five groups. Group A (n=3) is the control group. The right eyes of animals in Groups B,C, D, and E (n=3, resp.) were suffered with descemetorhexis procedures. From the 8th day to the 14th day postoperatively, the right eyes in Groups C and D were instilled with hyperosmolar drops and glyceraldehyde drops, respectively; the right eyes in Group E were instilled with both hyperosmolar drops and glyceraldehyde drops. Central corneal thickness (CCT), corneal transparency score, and histopathological analysis were applied on the eyes in each group. Results. Compared with Group A, statistically significant increase in CCT and corneal transparency score was found in Groups B, C, D, and E at 7 d postoperatively (P<0.05) and in Groups C, D, and E at 14 d postoperatively (P<0.05). Conclusion. Chemical CXL technique using glyceraldehyde improved the CCT and corneal transparency of the rabbit bullous keratopathy models. Topical instillation with glyceraldehyde and hyperosmolar solutions seems to be a good choice for the bullous keratopathy treatment.